2022
DOI: 10.3389/fpsyg.2022.1017645
|View full text |Cite
|
Sign up to set email alerts
|

Optimal BMI cutoff points in obesity screening for Chinese college students

Abstract: ObjectiveAn accurate BMI classification system specific to the population is of great value in health promotion. Existing studies have shown that the BMI recommended cut-off value for adults is not suitable for college students. Thus, the current study aims to identify optimal BMI cutoff points in obesity screening for Chinese college students.MethodsAnthropometric assessments were performed on 6,798 college students (Male = 3,408, Female = 3,390) from three universities in Jiangsu, China. Exploratory factor a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 55 publications
1
7
0
Order By: Relevance
“…Similar results were obtained for students from Saudi Arabia, with an average BMI of 22.75±1.91 kg/m 2 [17]. Wang et al [15] identified an optimal BMI of 23.53 kg/m 2 for male and 23.41 kg/ m 2 for female Chinese students. Arslan et al [18] defined the average BMI for students from Turkey: 22.94±3.30 kg/m 2 .…”
Section: Introductionsupporting
confidence: 71%
See 1 more Smart Citation
“…Similar results were obtained for students from Saudi Arabia, with an average BMI of 22.75±1.91 kg/m 2 [17]. Wang et al [15] identified an optimal BMI of 23.53 kg/m 2 for male and 23.41 kg/ m 2 for female Chinese students. Arslan et al [18] defined the average BMI for students from Turkey: 22.94±3.30 kg/m 2 .…”
Section: Introductionsupporting
confidence: 71%
“…• eating behavior and sleep quality [13,14]; • health standards [1,15]. Research results from different countries indicate some differences in BMI among both men and women.…”
Section: Introductionmentioning
confidence: 99%
“…After carefully reviewing the titles and abstracts, an additional 13 articles were eliminated. A comprehensive evaluation was conducted on a total of 35 articles, among which 10 were included in this meta-analysis (29)(30)(31)(32)(33)(34)(35)(36)(37)(38). There were no additional studies identified through manual search.…”
Section: Retrieved Resultsmentioning
confidence: 99%
“…Study in China was found lower cut-off of BMI for obesity screening than WHO recommendation. Optimal cut-off of BMI was found 23.53 kg/m 2 in male and 23.41 kg/m 2 in female 13 .…”
Section: Introductionmentioning
confidence: 91%